Grupos de Divisibilidade e Reticulados - Moura, Andréa Maria Ferreira (2010)
We present in this work a complete classification of the sublattices of (Zn,+, ≥) which are not groups of divisibility. Thus we provide a new class of ordered filtered groups of which are not groups of divisibility. The sublattices presented here generalize the exemples of P.Jaffard and G. G. Bastos